APPLICATION OF INVENTORY ACCOUNTING INFORMATION SYSTEM AN EFFORT TO IMPROVE INTERNAL CONTROL MATERIAL WAREHOUSE AT MODJOPANGGOONG SUGAR PLANT, TULUNGAGUNG - Khubatul Jannah (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2020)
Abstract: The application of inventory accounting information systems in the Modjopanggoong Tulungaung Sugar Factory material warehouse plays an important role in internal control. Internal control must be carried out properly so that there are no mistakes in carrying out existing procedures so as to minimize fraud. The study was conducted at the Modjopanggoong Sugar Factory Tulungagang which is engaged as a manufacturing company. This research uses a qualitative descriptive method involving 5 informants both internal and external informants. The results of this study that the application of accounting information systems in internal control for material inventory at the Modjopanggoong Sugar Factory is good although there are obstacles but it can still be resolved properly, because the employees in each section always carry out procedures well and the head office always oversees the activities of the Factory Modjopanggoong Sugar Tulungagung.